Clinicopathological features of thyroid Hürthle cell neoplasm in 73 cases - WANG Cuizhong, ZHONG Yichen, SHEN Tong, RUI Qiang, WANG Chenxi, JIANG Zhiwei, GONG Guanwen (Zhongguo linchuang yanjiu, 2025)
"Objective To explore the clinicopathological features of benign and malignant thyroid Hürthle cell neoplasm (HCN). Methods A retrospective analysis was performed on 73 patients diagnosed with HCN and underwent thyroid surgery in the Affiliated Hospital of Nanjing University of Chinese Medicine from January 2016 to June 2023. The patients were divided into Hürthle cell adenoma (HCA) group ( n =63) and Hürthle cell adenocarcinoma (HCC) group ( n =10) according to the postoperative pathological results. The clinicopathological features of the two groups were analyzed and compared. Logistic regression was used to analyze the influencing factors of malignant HCN, and their diagnostic efficacy for HCC was analyzed by receiver operating characteristic (ROC) curve. Results There was no significant difference between the two groups in general data, comorbidities, pathological features, thyroid function and immunohistochemical features ( P ＞0.05). The tumor diameter in HCC group was smaller than that in HCA group ［0.75 (0.38,1.00) cmvs 2.20 (1.25,3.15) cm,Z =2.595,P =0.009］, and the proportion of bilateral resection was higher than that in HCA group (30.00%vs 6.35%,P =0.049). Logistic regression analysis showed that the tumor diameter ( OR =0.311,P =0.022) and whether acepted bilateral resection ( OR =0.118,P =0.040) were independently related to HCC. ROC curve analysis revealed that the area under the curve (AUC) of mass diameter in the diagnosis of HCC was 0.756, the optimal cut-off value was 1.1 cm, with a sensitivity of 0.794, and a specificity of 0.800. Conclusion The size of the mass is of great significance for the judgment of HCA and HCC."